TI_GERICHTE 12.2023.72 vom 31. August 2023 , Contratto d'architetto globale, calcolo della mercede; uso e Regolamento SIA 102 - TI Tribunale d'appello (2023)
Contratto d'architetto globale, calcolo della mercede; uso e Regolamento SIA 102